Synthetic experimental and numerical investigation on the vertical seismic effect on underground structures. (February 2023) - Chen, Qingjun; Zhang, Tianyu; Hong, Na; Zhao, Zhipeng
Abstract: Seismic damage patterns of underground structures indicate unignorable effects of vertical seismic actions. To deal with this, this study distinguished the impact of the vertical seismic effect on the seismic safety of underground structures experimentally and theoretically and provides important shaking table test results for this topic. A typical shallow buried subway station-tunnel junction structure was designed by following the Buckingham similarity law, based on which the shaking table test was performed to investigate the vertical seismic effect on underground structures. The vertical wave propagation laws of the free field, the model structure, and the soil–structure interaction (SSI) system were comparatively analyzed. Numerical simulations considering the soil's nonlinear behaviors under vertical loads were performed using the equivalent linear analysis method and were verified by the test records. By combining both the experimental and numerical results, it was found that the surrounding soils have very weak constraints on the structural vertical movements. By distinguishing lateral soil pressures from horizontal actions, the vertical seismic action is found to be mainly an inertia force that can stimulate high-frequency vibration modes of the system and cause considerable vertical relative deformations within the underground structure. Consistent with the observed structural damage at the Daikai station, the participation of high-frequency vibration modes is a rational approach that can explain the amplification effect of vertical ground motions on structural seismic responses. In addition, the equivalent linear method is generally satisfactory for simulating the soil compressional nonlinearity.